Implikasi Literasi Asuransi Syariah Terhadap Tingkat Kooperatif, Komitmen, dan Loyalitas Nasabah - Wati, Lina (UIN Sunan Kalijaga Yogyakarta, 2022)
Research Aims: The purpose of the study was to determine literacy regarding sharia insurance and its relationship with the level of cooperation, commitment and loyalty to insurance companies. Design/methodology/approach: The approach used in this research is quantitative associative, with data analysis of Descriptive Statistics and Partial Least Square (PLS). This study uses the Theory of Planned Behavior (TPB) which is a matter of motivation and reason for a person in choosing and taking action, and what are the implications for a person's cooperative attitude, commitment and loyalty. The sample criteria required are as follows: people who use sharia insurance, people who have not used sharia insurance, people who are at least 20 years old with the assumption that respondents are capable of providing answers independently. Research Findings: Based on the test results, the literacy level of sharia insurance has positive and significant implications for cooperative attitudes, commitment, and loyalty to both customers and non-customers. Research limitation and implication: The implication is to find out how much influence literacy has in encouraging someone to choose to use sharia insurance. Keywords: Sharia Insurance, Literacy, Cooperative, Commitment, and Loyalty